Korgi. Book 3, A hollow beginning - Slade, Christian (Top Shelf, 2011)
When Ivy and Sprout discover a piece of stained glass in the woods, their curiosity leads them a quest to discover where it came from. In the process, they find a clue to the origin of their home, the Korgi Hollow.